When the Past Comes Knocking at My Front Door; My Name; & Favorite Shoes - Ariana Brown (Journal Committed to Social Change on Race and Ethnicity)
Ariana Brown is a queer Black Mexican American poet based in Houston, TX and the author of the poetry collections We Are Owed. (Grieveland, 2021) and Sana Sana (Game Over Books, 2020). Ariana is a national collegiate poetry slam champion, winner of two Academy of American Poets Prizes, and a recipient of a National Association of Latino Arts and Cultures Grant. She holds a BA in African Diaspora Studies and Mexican American Studies from UT Austin, an MFA in Poetry from the University of Pittsburgh, and an MS in Library and Information Science from the University of North Texas. She currently develops ethnic studies and ELA curriculum for high schools and colleges and teaches creative writing to teens in Houston.